Role of CT (Computed Tomography) in the Evaluation of Fungal Diseases in Paranasal Sinus - Islam, T; Azad, SA; Karim, ME; Khondker, L; Rahman, K (Journal of Bangladesh College of Physicians and Surgeons, 2014)
A cross sectional study carried out with patients having suspected paranasal sinus (PNS) mass during January 2009 to October 2010 to evaluate the fungal diseases in PNS by computed tomographic(CT) image and comparison of the findings of this modality with histopathological result. Among the total 76 patients, the mean age of the patients was 35.95 ± 18.24 and common complaints of the patients were nasal obstruction (73.7%) and maximum 53.9% patients had PNS mass in maxillary sinuses. Out of all cases 10 were diagnosed as having fungal infection/mass by CT scan and confirmed by histopathological evaluation. Two cases were diagnosed as having fungal infection/mass by CT scan but not confirmed by histopathological findings. Of 64 cases of other than fungal infection/mass, which were diagnosed by CT scan, six were confirmed as having fungal infection/mass and 58 were other than having fungal infection/mass by histopathology. Sensitivity of CT scan to diagnose fungal infection/mass was 62.5%, specificity 96.7%, positive predictive value 83.3%, negative predictive value 90.6% and accuracy 89.5%. CT scan of the fungal diseases in paranasal sinus provides more information and better image quality and CT diagnosis correlate well with the findings of histopathology. DOI: http://dx.doi.org/10.3329/jbcps.v31i4.21002 J Bangladesh Coll Phys Surg 2013; 31: 189-193